Mulheres Pagu e o tambor: experiências sonoras de pertencimento - Santos, Maria Carolina Simões dos (2021)
The drum and its vast symbolism combine with historical traces that point to the existence of a moment in history when women were the drummers. However, in modern history, with the advent of the patriarchal and capitalist system, female functions were restricted and redefined and the drum was removed and forbidden to be touched by women. The potential of Music and Music Therapy are present in social and cultural practices and establish an expressive and creative channel of communication, promoting health and well-being in community contexts. Additionally, in recent years both provide musical experiences as strategies for female empowerment. In the current, fourth wave of Brazilian feminism, there is an appropriation of spaces, traditionally considered of male chauvinist rhetoric. One of the most expressive examples of the presence of women in popular culture is the street Carnival, with the appearance of numerous groups composed of women. Through the experience of eight women, rhythmists of the Pagu Carnival group, it was possible to access, through semi-structured interviews in a qualitative research, material for analysis. The objectives were to understand the motivations, meaning and impacts generated from drum practices, as well as their possible associations with the psychological well-being of these women. Using the Thematic Analysis method, themes arose which demonstrated and gave meaning to the strong connective appeal engendered in the union of drums and women. This activity created support and strengthened networks. Personal growth, self-acceptance and autonomy also appear as results of this encounter, transforming these collective musical practices into true sound experiences of belonging